Outcome of Non-drainage Scleral Buckling in Primary Rhegmatogenous Retinal Detachment - Agarwal, Lalit; Agrawal, Nisha (Nepalese Journal of Ophthalmology, 2021)
Introduction: Scleral buckling (SB) was the principal surgical intervention for patients with rhegmatogenous retinal detachment (RRD) until the development of pars plana vitrectomy. The study aims to evaluate the outcome of SB without subretinal fluid (SRF) drainage in RRD. Materials and methods: A retrospective observational study was conducted at a tertiary eye care center. Charts of patients operated with SB without SRF drainage for RRD between January 2014 and December 2015 were evaluated. The main outcome measure was the primary reattachment rate at 1 month after single SB surgery. Other outcome measures were final reattachment rate after further intervention, visual improvement and relation of various parameters with retinal reattachment. Results: One hundred and seventeen patients were included of which 90 (76.9%) were men. Mean age was 26.68±12.6 years (Range 9-60). All eyes were phakic. Only 1 patient had a macula on RD. The primary reattachment rate was 84.6% (n=99). Mean LogMAR (±SD) visual acuity (VA) improved from 1.92(±0.46) to 1.02(±0.42). Extent of RD, number of breaks, and type of break was found to have no association with retinal reattachment. Association between type of PVR and status of retina post buckling was found to be significant (p=0.026) with retinal reattachment seen in 100% in PVR-A and only 60% in PVR-C2. Final reattachment rate was 98.2%. Complications encountered were postoperative diplopia (n=1), suture granuloma (n=1) and buckle infection (n=2). Conclusion: Scleral buckling without SRF drainage, an exclusively extra ocular procedure, is an effective and safe treatment modality for non-complicated RRD.